If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6+9=5(3x-3)
We move all terms to the left:
6+9-(5(3x-3))=0
We add all the numbers together, and all the variables
-(5(3x-3))+15=0
We calculate terms in parentheses: -(5(3x-3)), so:We get rid of parentheses
5(3x-3)
We multiply parentheses
15x-15
Back to the equation:
-(15x-15)
-15x+15+15=0
We add all the numbers together, and all the variables
-15x+30=0
We move all terms containing x to the left, all other terms to the right
-15x=-30
x=-30/-15
x=+2
| 4-3x=9x-8 | | (n+8)=+9 | | 10=k3+ 8 | | -r-1=-9-2r | | 2(8x+8)=48 | | 7/9x-8=x | | 12x+42=6(2x+7) | | 15x-2x-7=-14x-25 | | 180-x=490-6x | | 4x-34=82 | | 4(3m+3)=96 | | -4w-12=2(w-3) | | 9x-24+6x-5=x+9 | | 8-k=-10+8k | | 4w+15=−13;w4w+15=−13;w | | 113=-10a-7 | | 2(3+5x)=37 | | 8(4x+2)-6x-5=2(13x-4)+19 | | -2(10w+8)=-16w+20 | | (-54y-27)=-18 | | 7(y-2)+2y=-3(y+4)-2y | | -6(a-3)=11-7a | | 8n=5n-8 | | x^2+24-12=0 | | 3(2x+7)=40+25 | | 36-6y=12 | | 3(2x+4)=2(-6x-3) | | 12+8x=x-16 | | 3(r+1)=-25-4r | | 9x+4+3x+9=90 | | -9x+23=7x-41 | | r-6=6(8-3r) |